Prevention of Allergic Contact Dermatitis: Safe Exposure Levels of Sensitizers - Uter, Wolfgang; Johansen, Jeanne Duus (Springer International Publishing, 2020)
Contact allergy and allergic contact dermatitis are environmental diseases caused by excessive exposure to sensitizing substances in products, such as cosmetics, other consumer items, occupational products, etc. It is possible to prevent the occurrence of these diseases by limiting exposure. This can be done by various methods, such as information, avoidance/protection, restriction of the ingredients to safe levels, or ban. These different methods are reviewed, and examples of the effect of different interventions are given.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Exposure; Hazard information; Labelling; Regulation; Risk assessment; Risk management